English for Specific Purposes in the Digital Era:: Integrating Needs Analysis, AI Literacy, and Work Readiness among Students of the Faculty of Teacher Training and Education at Ekasakti University - Martha Suri, Elda; Novalia Jufri, Windry; Ifana Silaban, Ririn (International Journal of Language Teaching and Education, 2026)
This study examines the relevance of English for Specific Purposes (ESP) in the digital era by integrating needs analysis, AI literacy, and work readiness among students of the Faculty of Teacher Training and Education at Ekasakti University. The study is motivated by the increasing demand for prospective teachers to possess not only general English proficiency, but also academic, professional, digital, and AI-supported communication skills. A mixed-method approach was employed, involving questionnaires, interviews, and document analysis to identify students’ English learning needs, their awareness and use of AI tools, and their readiness to enter the teaching profession. The findings indicate that students need more contextual ESP materials related to educational terminology, academic reading, classroom communication, teaching material development, professional presentation, and digital communication. The study also reveals that AI literacy plays an important role in supporting students’ English learning, particularly in improving writing, enriching vocabulary, understanding academic texts, preparing presentations, and developing learning resources. However, students need guidance to use AI critically, ethically, and responsibly. The novelty of this study lies in the integration of needs analysis, AI literacy, and work readiness within ESP learning for prospective teachers. The study implies that ESP courses should be developed as needs-based, technology-supported, and career-oriented learning programs to strengthen students’ English competence, digital literacy, professional communication skills, and readiness for the modern teaching profession.